Carbon tattooing for targeted lymph node biopsy after primary systemic therapy in breast cancer: prospective multicentre TATTOO trial. Issue 3 (23rd January 2021) - Hartmann, S; Kühn, T; de Boniface, J; Stachs, A; Winckelmann, A; Frisell, J; Wiklander-Bråkenhielm, I; Stubert, J; Gerber, B; Reimer, T
Abstract: Background: Several techniques for targeted lymph node biopsy in patients with node-positive breast cancer receiving primary systemic therapy are in use, each with their inherent advantages and disadvantages. The aim of the TATTOO trial was to evaluate the feasibility and accuracy of carbon tattooing of positive lymph nodes as a method for targeted lymph node biopsy avoiding radiation exposure, high costs, and preoperative localization procedures. Methods: Patients with initially cT1–4c cN1–3 cM0 invasive breast cancer were included in this prospective multicentre trial. Before initiation of primary systemic therapy, a carbon suspension was injected into the most suspicious axillary lymph node. Targeted lymph node biopsy was performed in all patients after completion of primary systemic therapy. Additional sentinel lymph node biopsy was done in those with axillary downstaging, and completion axillary lymph node dissection in patients still presenting with suspicious lymph nodes. Results: A total of 118 patients were included and 110 were eligible for data analysis. The detection rate for the targeted lymph node was 93.6 per cent (103 of 110), and the sentinel lymph node was identical to the targeted lymph node in 60 per cent. The false-negative rate for the combination of targeted and sentinel node lymph node biopsy (targeted axillary dissection) was 9 per cent. Conclusion: Targeted axillary dissection after carbon tattooing is associated with a high detection rate, an acceptable false-negative rate, and appears feasible for clinical use even in healthcare settings with limited resources. Abstract : The prospective multicentre TATTOO trial included 118 patients with initially node-positive breast cancer. Before primary systemic therapy the target lymph node was tattooed using carbon particles under ultrasound guidance. The trial revealed an intraoperative detection rate of 93.6 per cent for the tattooed node and an acceptable false-negative rate of 9 per cent for targeted axillary dissection. Easy and reliable